Analisa Trend Peningkatan Jasa Branding JCK Enterprise Surabaya Selama Pandemi COVID-19 - Florencia Irena; Galih Wicaksono (Universitas Ciputra Surabaya, 2022)
In the current digital era, there are many ways that a business actor, either individually or in a company, can continuously improve the branding quality of his own business. One way to improve the quality of branding is to use the services provided by creative agencies. This study aims to analyze the development and impact of branding services on creative agencies in Surabaya during the Covid-19 pandemic. Because through this analysis, we will know the flow of branding service users in the Surabaya area for creative workers during the Covid-19 pandemic. The research method used in this study is qualitative, data collection is carried out by conducting interviews with the founder of JCK Enterprise as the subject of observation, this research is also supported by journal sources, and articles related to creative agencies, branding services, and the covid-19 pandemic. Keywords: branding service, Creative agency, Covid-19 Pandemic